115k views
24 votes
I saved the best for last :]

I saved the best for last :]-example-1
User Mranders
by
5.5k points

1 Answer

5 votes

Answer:

a¹⁸b²⁴c⁵⁴

Explanation:

(aᵇ)ᶜ = aᵇᶜ = aᵇ×ᶜ

(-aⁿ)ᵒᵈᵈ = -aⁿ

(-aⁿ)ᵉᵛᵉⁿ = aⁿ

aⁿ × aⁿ = aⁿ⁺ⁿ

_________

In this situation, 6 is an even exponent which means that the negative coefficient of this 9th degree monomial will be positive. Now the only step is to multiply the exponents by the exponent outside of the perenthesis which is 6.

so (-a³b⁴c⁹)⁶ = ((-a³)⁶(b⁴)⁶(c⁹)⁶) = ((a³ˣ⁶)(b⁴ˣ⁶)(c⁹ˣ⁶)) = ((a¹⁸)(b²⁴)(c⁵⁴)) = a¹⁸b²⁴c⁵⁴

User Morteza Jangjoo
by
5.7k points